Предмет:
АлгебраАвтор:
zaviermcintyreа) m + 3n - 3m²n - m³ = m + 3n - m²(3n + m) = (3n + m)(1 - m²) = (3n + m)(1 - m)(1 + m).
б) 2a⁴ + a³b - 2a - b = a³(2a + b) - (2a + b) = (2a + b)(a³ - 1) = (2a + b)(a - 1)(a² + a + 1)
Автор:
jeremy5Ответ:
Объяснение:
m(1-m²)+3n(1-m²)= (m+3n)(1-m)(1+m)
2a(a³-1)+b(a³-1)= (2a+b)(a-1)(a²+a+1)
Автор:
jamya1no1Добавить свой ответ
Предмет:
Русский языкАвтор:
janmcneilОтветов:
Смотреть
Предмет:
ЛитератураАвтор:
milo77hzОтветов:
Смотреть
Предмет:
МатематикаАвтор:
athenaОтветов:
Смотреть